An analysis of fuzzy clustering algorithms for suggestion of supervisor and examiner of thesis title [microfilm] - 361495 Azrina Suhaimi (Skudai : Universiti Teknologi Malaysia, 2005)
Thesis (Sarjana Sains (Sains Komputer)) - Universiti Teknologi Malaysia, 2005